Review of Biological Properties, Composition and Toxicity of Annonna Muricata - Algeryani, Safa A. (Scientific Journal of University of Benghazi, 2020)
Annona muricata also known as a Grviola is a fruit tree with a long history of traditional use. A. muricata, has a wide array of ethnomedicinal activities and containing wide range of chemical compounds including Alkaloids (acetogenins); which represent the major constituents of A. muricata, there were more than 100 annonaceous acetogenins have been isolated from leaves, barks, seeds, roots and fruits of A. muricata. Furthermore; lipids, isoquinoline, lactones, Annomuricatina (protein), Bullatacin and Muricoreacinetc have been isolated from this plant. The plant extracts and Secondry metabolites exhibit pharmacological properties such as anti-inflammatory, antibacterial, antioxidant, antiparasitic, hepatoprotective and bilirubin-lowering, anti-diabetic, wound healing, antiobesity, immunomodulatory, and anticancer activity. The present review summarizes the information concerning the traditional uses, phytochemistry, biological activity and two case studies one in vitro on pancreatic cancer cells and other in vivo study on breast cancer that had been carried recently to assess the effects of Graviola.